Extraction of recombinant proteins from Escherichia coli by cell disruption with aqueous solutions of surface-active compounds - Martins, Margarida; Ooi, Chien Wei; Neves, Márcia C; Pereira, Jorge F B [UNESP]; Coutinho, João A P; Ventura, Sónia P M (Wiley, 2018)
BACKGROUND: Green fluorescent protein (GFP) is used extensively as a biomarker due to its unique spectral and fluorescence characteristics. GFP is usually obtained from recombinant strains of Escherichia coli (E. coli) producing the protein intracellularly. However, the common methods of extraction are cumbersome leading to an increase in the downstream process costs and complexity, sometimes leading to a higher risk of biomolecule degradation. RESULTS: This work proposes a new method to extract recombinant intracellular GFP from E. coli BL21 by using aqueous solutions of surface-active compounds. CONCLUSION: By comparing the fluorescence intensity of the extracted GFP, it was concluded that some of these compounds, namely ionic liquids with an alkyl chain of 10 or more carbons (best solvent being tributyl-1-tetradecylphosphonium, [P4,4,4,14]Cl) are more effective than an ultrasonic-assisted extraction, even at low concentrations, being able to extract the whole GFP content from the cells. © 2018 Society of Chemical Industry.
Keywords: cell disruption; extraction; green fluorescent protein; intracellular protein; recombinant proteins; surface-active compounds